Hubungan Standar Keamanan Pasien terhadap Insiden Keselamatan Pasien di Rumah Sakit Pertamedika Ummi Rosnati Banda Aceh - Zawil Muna; Urip Pratama; Khaira Rizki (Lembaga Pengembangan Kinerja Dosen, 2024)
Incidents and patient safety in hospitals are very important things in the service system. Based on data from the World Health Organization (WHO), in 2020, every year there were 134 million reports related to patient safety incidents and caused 2.6 million patient deaths in hospitals. This study aims to determine the relationship between patient safety standards and patient safety incidents at the Pertamedika Ummi Rosnati Hospital, Banda Aceh. This type of research is a descriptive analytical research with a cross sectional study design. The population used in this study were all nurses, totaling 138 nurses. Sampling in this study was carried out by random sampling (random probability) with a purposive sampling technique with a total of 58 respondents. For patient safety standards, 43 people (74.1%) stated that patient safety standards had been implemented in accordance with hospital operational service standards, and only 15 people (25.9%) said they had not. 38 people (65.5%) stated that patient safety incidents were a standard priority for the hospital and only 20 people (34.5%) stated that this did not mean that patient safety incidents were less of a priority for nurses. The results of the bivariate test prove that there is a significant relationship between patient safety standards and patient safety incidents with a P-value = 0.019. The conclusion is that there is a relationship between patient safety standards and patient safety incidents.